Modification and In Vitro Biological Evaluation of Ceftriaxone-Imine Derivatives: Possible Anticancer and Antimicrobial - Reem Alaulddin Jameel; Balsam Mohammed Ahmed; Raghad Haddad (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research investigates the modification of ceftriaxone to synthesized imine derivatives (A-C), assessing their chemical and biological efficacy. This study underscores the notable antibacterial effectiveness of synthesized derivatives against Staphylococcus aureus and Escherichia coli, exhibiting a determined dose correlation. The synthesis procedure reacts ceftriaxone with different aldehydes, such as 2-Hydroxy-4-Methoxybenzaldehyde and 4-ethoxy-2-hydroxy-benzaldehyde, and 5-Chloro-2-hydroxybenzaldehyde yielding imines analyzed by various methods, such as FT-IR and 1H-NMR. The results indicate that imines may have implications in medical therapies, especially in addressing multidrug-resistant bacteria and a human breast cancer cell line MCF-7. Imine derivative C exhibits significant antibacterial efficacy, measuring 33 mm at 0.1 ppm against Staphylococcus aureus, while 30 mm at 0.1 as anti-Escherichia coli more activity from other synthesized derivatives. The derivative C recorded a value of 29.2441 after 24 hours as an inhibition MCF-7 cell line.